A Case of Inoperable Malignant Insulinoma with Resistant Hypoglycemia Who Experienced the Most Significant Clinical Improvement with Everolimus - Emre Bozkirli; Okan Bakiner; Huseyin Abali; Cagatay Andic; Ali Fuat Yapar; Fazilet Kayaselcuk; Eda Ertorer (Case Reports in Endocrinology)
Metastatic insulinomas may sometimes present with recurrent life-threatening hypoglycemia episodes. Such patients usually fail to respond to various therapeutic agents which causes constant dextrose infusion requirement. Herein, we present a resistant case of inoperable malignant insulinoma who was treated with many therapeutic agents and interventions including somatostatin analogues, Yttrium-90 radioembolization, everolimus, radiotherapy, and chemoembolization. Close blood sugar monitorization during these therapies showed the most favourable response with everolimus. Everolimus treatment resulted in rapid improvement of hypoglycemia episodes, letting us discontinue dextrose infusion and discharge the patient. However, experience with everolimus in such patients is still limited, and more precise data can be obtained with the increasing use of this agent for neuroendocrine tumours.